Efficacy and Safety of Busulfan‐Based Conditioning Regimens for Multiple Myeloma. (29th April 2013) - Reece, Donna; Song, Kevin; LeBlanc, Richard; Mezzi, Khalid; Olujohungbe, Ade; White, Darrell; Zaman, Faraz; Belch, Andrew
Abstract : Multiple myeloma is a malignancy of B cells characterized by accumulation of abnormal plasma cells in the bone marrow. In the past 20 years, the use of high‐dose therapies and novel agents has resulted in significant and meaningful improvements in survival. Autologous stem cell transplantation (auto‐SCT) following a high‐dose melphalan‐conditioning regimen represents the standard of care for younger patients as well as older patients with a good performance status. A number of strategies have been proposed to improve the outcome of auto‐SCTs, including the incorporation of new agents such as thalidomide, lenalidomide, and bortezomib into the induction regimen administered before auto‐SCT; the administration of maintenance therapy after auto‐SCT; the incorporation of novel agents into chemotherapeutic regimens after transplantation as consolidation therapy; and the use of reduced‐intensity allogeneic transplantation after an initial autograft. Although these approaches have demonstrated some success in improving responses after auto‐SCT, none of these strategies are curative. An additional strategy to improve outcomes after auto‐SCT is to enhance the immediate pretransplant conditioning regimens by either increasing the dose of melphalan or by incorporating novel agents, such as busulfan. This literature review focuses on the efficacy and safety of busulfan‐based conditioning regimens for auto‐SCT in patients with multiple myeloma. Abstract : This literature review focuses on the efficacy and safety of busulfan (BU)‐based conditioning regimens for autologous stem cell transplantation in patients with multiple myeloma. A BU‐melphalan regimen demonstrated superior efficacy and a satisfactory safety profile, particularly when the i.v. formulation of BU was used.